Moringa (Moringa oleifera) leaves extract gel improved wound healing by increasing fibroblasts, neovascularization and in male Wistar rats - Citra Anissa Ayu; I Wayan Weta; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Background: Wound healing can be accelerated by the supplementation of naturalcompound especially flavonoids and tannins. These compounds is known to be abundant in several plant species such as moringa (Moringa oleifera). Therefore, the aim of this study was to assess the effect of moringa leaves extract gel toward wound healing rate in in male Wistar rats (Rattus norvegicus). Methods: This research was a true experimental study using randomized post-test only control group design. Subjects were 28 rats (Rattus norvegicus), males, 5-6 months old, weighing 200-250 gram, which were divided into four groups (n= 7 rats) randomly. The first group was treated with placebo for 4 days (P0(4)), the second group was treated with moringa leaves extract gel for 4 days (P1(4)), the third group was treated with placebo for 11 days (P0(11)), and the fourth group was treated with moringa leaves extract gel for 11 days (P1(11)), and the last of intervention carried out measurements of fibroblast cell , neovascularization and epithelialization. Results: Administration of moringa leaves extract gel significantly increased the fibroblast density, neovascularization, and epithelial thickness. However, despite increased density of fibroblast and neovascularization at day 4, they significantly dropped at the second measurement (day 11). On the other hand, epithelial thickness was consistently improved overtime compared to control. Conclusion: The Moringa oleifera leaves extract gel improved wound healing by speeding healing process and epithelialization in male wistar rats (Rattus norvegicus).